Nie tylko z drewna. Wiadra klepkowe obite blachą w grobach wczesnośredniowiecznych na terenie ziem polskich - Tomasz Kurasiński (Przegląd Archeologiczny)
In this study, information was collected on stave-built wooden vessels (buckets) from early medieval cemeteries in Polish lands, for which the distinguishing feature is metal fittings in the form of strips and / or crescent- shaped applications. In the light of the current state of knowledge, we have information on 33 containers of such design from nineteen cemeteries. The most numerous collection of them was discovered in Lutomiersk, from where eight graves with such vessels are known. Three containers were recorded in the cemetery in Pień, and in Kałdus, Lubień, Komorowo and Poznań-Śródka – two in each. The remaining sites provided single finds. These vessels were subjected to a typological, formal and chronological analysis, taking into account the context of discovery and provenance, and on this basis an attempt was made to interpret their meaning in funeral rites. In Polish lands, the deceased were buried with the type of vessel in question at the end of the 10th century, and this custom disappeared at the beginning of the 12th century.